Efficacy of erlotinib in NSCLC harboring rare EGFR extracellular domain mutation (T263P) and common mutations: Case report and literature review - Wang, Qian; Wang, Yong; Zhang, Xinwei; Fang, Chen; Qian, Xiaoying; Li, Yong (Frontiers in Oncology, 2022)
The epidermal growth factor receptor (EGFR) typically contains an extracellular domain (ECD), a transmembrane (TM) domain, and an intracellular kinase (KD) domain. ECD mutations of EGFR in NSCLC may affect its normal function and intrinsic resistance to tyrosine kinase inhibitors (TKIs) and the effectiveness of drugs for these patients is unsatisfactory. Recently, we found an EGFR T263P mutation located at the ECD, which has never been reported in Chinese non-small cell lung cancer (NSCLC). Hence, we reported that a patient with advanced lung adenocarcinoma harboring the EGFR T263P mutation, L858R mutation and MET amplification was resistant to osimertinib but significantly benefited from erlotinib and capmatinib treatment. This patient achieved a partial response and had progression-free survival (PFS) for more than 19 months. In summary, we are the first researchers to report in detail on a Chinese patient carrying the T263P mutation and summarize all the ECD mutations in NSCLC. We believe this finding will enlighten us to treat patients with EGFR ECD mutations and more patients deserve further study.